IMPLEMENTATION OF ENVIRONMENTAL FIQH IN INDONESIA FROM THE PERSPECTIVE OF MAQĀṢID AS-SYARĪ’AH JASSER AUDA - Makraja, Fahmi; Ramlah, Ramlah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The aim of implementing sharia (maqashid sharia) is to maintain a better order of life. In Indonesia, environmental aspects still need serious attention, so the presence of this research is to actualize the concept of environmental jurisprudence in Indonesia from the perspective of Jasser Auda's Maqāṣid As-Syarī’ah . The method used in this research is descriptive qualitative with a library approach. The aim of this research is to provide an overview and solution to the implementation of environmental jurisprudence (fiqh bī’ah) in Indonesia based on Jasser Auda's maqashid sharia concept. The research results show that environmental problems in Indonesia have not been resolved comprehensively, marked by various natural disasters, waste and significant climate change. This needs to be discussed, considering the long continuity of human life, so it is important to implement awareness to protect the environment through the actualization of environmental jurisprudence in society. This is explained in the actualization of environmental jurisprudence based on Jasser Auda's concept of maqashid sharia where preserving the environment is part of maintaining religion, soul or honor, reason, lineage and property. So the concept of Environmental Jurisprudence (fiqh al-bī'ah) with an ecoreligious typology is very important to apply in Indonesia